Analysing supplier selection criteria in fertigation system using fuzzy DEMATEL method / Ainun Hafizah Mohd ... [et al.] - Mohd, Ainun Hafizah; Ramli, Nazirah; Abd Nassir, Asyura; Mohd Bahkri, Nur Hazirah (Universiti Teknologi MARA Cawangan Pahang, 2020)
In the agricultural field, the fertigation system helps improve root activity, nutrient mobility and uptake, besides decreased pollution of groundwater. A well-designed fertigation system should be combined with a suitable selection of materials and equipment. Various criteria should be considered throughout the process of making decision on selecting the right suppliers. Thus, the purpose of the study is to analyse the selection criteria of the supplier in fertigation system using fuzzy DEMATEL method. The present study focuses on six criteria of supplier selection; price, quality, delivery, public procurement policy, technical and managerial which are relevant for fertigation system. This study incorporates questionnaires from expert interviews to evaluate the significance of criteria involved in supplier selection. Data collected from experts in the field of fertigation system were analysed using fuzzy DEMATEL method. The findings show that public procurement policy is the most influential criteria for supplier selection in fertigation system.